The professional ethic and the spirit of post-modernism: Researching values in teaching and research in the education of adults - Paul Armstrong (Adult Education Research Conference, 1996)
This paper reports on a research project being undertaken in Britain to find out whether those involved in university teaching and research in the education of adults need a code of ethics, and how the research question has been transformed into ‘why is this question being asked at this time?’ The answer, it is suggested, has something to do with the post-modern condition.